An Overview Of Virtualization (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This paper presents an overview of virtualization .The first part covers the various Virtualization approaches. The second part covers the requirements for virtualization and its working. The third part covers its applications. In the final part the challenges and security issues are discussed. Â